Studi model rancangan hunian vertikal berdasarkan bentuk interaksi warga di bantaran sungai Winogo Yogyakarta - Sidhi Pramudito; Antonius Lanang Tegar Wicaksana Praptantya; David Jeffry Nasir (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2019)
Riverbanks are one of the urban areas that often experience decrease in its environment quality. This is caused by the improper utilization of riverbanks as a living space. Consequently, the quality of adequate housing for the community is difficult to achieve. Although the government has tried to build flats as a solution to the problem, some residents choose to abandon them because of its formal and rigid vertical dwelling model that make the residents feel lack of togetherness and interaction between community. This kind of communal perspectives sometimes cannot be found when they live in horizontal dwelling (kampung). The purpose of this paper is to generate recomendation for a vertical dwelling model based on the form of community interaction in Kampung Gampingan, located at the Winongo River. The paper is expected to be an alternative solution for stakeholders in planning and designing settlements, especially in villages on the banks of urban rivers. © 2019 Sidhi Pramudito, Antonius Lanang Tegar Wicaksana Praptantya, David Jeffry Nasir